A simple model to predict long-range atomic ordering temperatures in Cu-based shape memory alloys - Pelegrina, Jorge Luis (2014)
The order–disorder and order–order phase transition temperatures in the austenitic phase of Cu-based shape memory alloys were used to obtain a set of first- and second-neighbour pair interchange energies. To this end, a mean field model was postulated. Then, the applicability to different alloys of this simple model was analysed. It was found that a good agreement with the experimental phase diagram is obtained for Cu–Zn–Al, Cu–Al–Ni and Cu–Al–Be alloys using composition-independent parameters. It was also found that for Cu–Al–Mn alloys, composition-dependent pair interchange energies need to be employed.